Association of matrix metalloproteinase 2 plasma level with response and survival in patients treated with bevacizumab for recurrent high-grade glioma. Issue 3 (9th December 2013) - Tabouret, Emeline; Boudouresque, Françoise; Barrie, Maryline; Matta, Mona; Boucard, Celine; Loundou, Anderson; Carpentier, Antoine; Sanson, Marc; Metellus, Philippe; Figarella-Branger, Dominique; Ouafik, L'Houcine; Chinot, Olivier
Abstract: Background: A predictive marker of bevacizumab activity is an unmet medical need. We evaluated the predictive value of selected circulating prebiomarkers involved in neoangiogenesis and invasion on patient outcome in recurrent high-grade glioma treated with bevacizumab. Methods: Analyzed in plasma were a set of 11 prebiomakers of interest (vascular endothelial growth factor receptor [VEGF]; VEGF receptor 2; basic fibroblast growth factor; stromal cell derived factor 1; placenta growth factor; urokinase-type plasminogen activator; plasminogen activator inhibitor 1; matrix metalloproteinases 2, 7, and 9; and adrenomedulline), using ELISA, at baseline and 2 weeks after bevacizumab initiation in a prospective cohort of 26 patients (Cohort 1). Correlations were validated in a separate retrospective cohort (Cohort 2; n = 50) and tested in cohort patients treated with cytotoxic agents without bevacizumab (Cohort 3; n = 34). Dosages were correlated to objective response, progression-free survival (PFS), and overall survival (OS). Results: In Cohort 1, high MMP2 baseline level was associated with a probability of objective response of 83.3% versus 15.4% for low MMP2 level ( P = .001). In multivariate analysis, baseline level of MMP2 correlated with PFS (hazard ratio, 3.92; 95% confidence interval [CI]:1.46–10.52; P = .007) and OS (hazard ratio, 4.62; 95% CI: 1.58–13.53; P = .005), as decrease of VEGF ( P = .038 for PFS and P = .013 for OS) and MMP9 ( P = .016 for PFS and P = .025 for OS). In Cohort 2, MMP2, but not MMP9, confirmed its predictive significance. In Cohort 3, no association was found between MMP2, MMP9, and outcome. Conclusion: In patients with recurrent high-grade glioma treated with bevacizumab, but not with cytotoxic agent, high MMP2 plasma levels are associated with prolonged tumor control and survival. MMP2 should be tested in randomized clinical trials that evaluate bevacizumab efficacy, and its biological role reassessed.